Peran Guru PAI Dalam Mengembangkan Sumber Belajar PAI di SMP Negeri 2 Rejang Lebong - mutiara sendi, okni aisa; Karolina, Asri (Program Studi Pendidikan Agama Islam, 2022)
Learning assets become the fundamental wellspring of learning in the execution of educator learning plays a significant part in the achievement of learning. The reason for this study needs to discover how the job of PAI instructors in creating PAI learning assets in SMP Negeri 2 Rejang Lebong. The strategies utilized subjectively by information assortment through talk with methods, perceptions and documentation and broke down utilizing miles et al approach are information decrease, information show and end withdrawal. This examination inferred that the job of PAI educators in creating PAI learning assets in SMP N 2 Rejang Lebong is by overseeing classes planning learning as per the metari to be instructed. Different learning assets will be utilized in the learning system adjusted to the material to be conveyed. Learning assets like printed books, modules, lks, pictures, then, at that point, it can likewise be with ecological items in schools, trees, or other plants.the utilization of instructor handbooks, lks, modules, existing books, mosques or mosques, then, at that point, school and educator conditions, online books or diaries, recordings, pictures, films that will give material. The learning media utilized in creating PAI learning assets in SMP Negeri 2 Rejang Lebong is the utilization of powert focuses, sound, pictures, banners, cardboard, radio, film, video.